Excessive Evidence, as an Anomaly of Searching for Truth in Criminal Proceedings (Academic Journal of Internal Affairs, 2022)
Aim: Concerning excessive evidence – beyond the quantity of evidence that is necessary to decide on the issue of guilt – it is a widespread opinion that it is nothing more than a deflection, an anomaly, that is detrimental to the economy of the procedure. This paper aims to present that the problem of excessive evidence is far more complicated than a merely practical issue.Methodology: I attempt to analyze the methods of seeking truth in criminal proceedings, or other words, excessive evidence as a dysfunction of fact-finding in the court stage of criminal proceedings.Findings: One part of the concluding thoughts are that excessive evidence is by no means just a secondary problem in forensics. Its roots derive from the fundamental issue of the search for truth and justice, as well as the functions of criminal proceedings since excessive evidence is originally an anomaly in the search for truth. In my view, this explains why it is not possible to get rid of it with methodological guidelines or recommendations for cost-efficient investigation and litigation. Consequently, excessive evidence must not only be seen as an unnecessary delay of criminal proceedings. It may also raise other significant guarantee concerns, thus undermining the rule of law in several directions at the same time.Value: This paper also points out the solutions that the Act XC of 2017 on Criminal Procedure ensures about the problem of excessive evidence.
Keywords: searching for truth; excessive evidence; shared functions; the preparatory meeting